Manassantin A and B From Saururus chinensis Inhibit Interleukin-6–Induced Signal Transducer and Activator of Transcription 3 Activation in Hep3B Cells - Jong Sun Chang; Seung Woong Lee; Myo Sun Kim; Bo Ra Yun; Mi Hye Park; Seok-Geun Lee; Su-Jin Park; Woo Song Lee; Mun-Chual Rho (Journal of Pharmacological Sciences, 2011)
Inhibition of interleukin-6 (IL-6) has been postulated to be an effective therapy in the pathogenesis of several inflammatory diseases. The current study was performed to examine potential effects of manassantin A and B isolated from Saururus chinensis on the IL-6–induced response to human hepatoma cells. We found that manassantin A and B inhibit signal transducer and activator of transcription 3 (Stat3) activity stimulated by IL-6. We also found that both compounds decreased IL-6–induced Stat3 phosphorylation and nuclear translocation. Both compounds blocked suppressor of cytokine signaling 3 (SOCS-3)-mRNA expression induced by IL-6. In addition, we found that Stat3 inhibitory effects of these compounds could be related to protein tyrosine phosphatase. These findings suggest that manassantin A and B could be useful remedies for treatment of inflammatory diseases by inhibiting IL-6 action. Keywords:: manassantin A and B, interleukin-6, signal transducer and activator of transcription 3 (Stat3)